Assessment of root canal anatomy of maxillary and mandibular canine teeth : a cone-beam computed tomography study = Evaluación de la anatomía del canal radicular de caninos maxilares y mandibulares : un estudio de tomografía computarizada de haz cónico - Okumuş, Özlem; Çoban Kanyılmaz, Ata Nisa (2022)
To investigate the root canal anatomy of permanent maxillary and mandibular canines in a Turkish subpopulation using cone beam computed tomography (CBCT). Retrospective CBCT data of 300 patients admitted to our clinic between 2016 and 2018 were screened and evaluated. A total of 235 patients, 100 males and 135 females, aged 14-76 years (mean age 37.27±13.40) were included in this study. A total of 191 (44,8%) maxillary canine teeth and 235 (55,2%) mandibular canine teeth were examined. The number of roots and root canal morphology according to Vertucci's classification, the presence of accessory canals, and the position of the apical foramen of the root were analyzed. The effect of gender and age on the incidence of root canal morphology was also investigated. The majority of the teeth had a Type I canal configuration in both maxillary canines (100%) and mandibular canines (92,8%). In the mandibular canines the other canal patterns found were Type III (6,8%), and Type II (0,4%). Apical foramen was centrally positioned in the majority of the teeth, 70,2% and 66,8% in maxillary and mandibular canines, respectively. The occurrence of two roots in mandibular canines was 3,8% and the root canal separation was found 53,8% and 46,2% in the middle and cervical third of the root, respectively. No significant statistical difference was observed effect of gender and age on the incidence of the root canal morphology and the position of the apical foramen. Due to the diverse morphology and the potential presence of a second canal for canine teeth among the Turkish subpopulation, dentists should perform endodontic treatments with greater care. CBCT is an accurate tool for the morphological assessment of the root canals.
Investigar la anatomía del conducto radicular de los caninos maxilares y mandibulares permanentes en una subpoblación turca utilizando la tomografía computarizada de haz cónico (CBCT). Se examinaron y evaluaron los datos CBCT retrospectivos de 300 pacientes ingresados en nuestra clínica entre 2016 y 2018. Un total de 235 pacientes, 100 hombres y 135 mujeres, de entre 14 y 76 años (edad media de 37,27±13,40) fueron incluidos en este estudio. Se examinaron un total de 191 (44,8%) dientes caninos maxilares y 235 (55,2%) dientes caninos mandibulares. Se analizó el número de raíces y la morfología del conducto radicular según la clasificación de Vertucci, la presencia de conductos accesorios y la posición del foramen apical de la raíz. También se investigó el efecto del sexo y la edad en la incidencia de la morfología del conducto radicular. La mayoría de los dientes tenían una configuración de conductos de tipo I tanto en los caninos maxilares (100%) como en los caninos mandibulares (92,8%). En los caninos mandibulares los otros patrones de conductos encontrados fueron el Tipo III (6,8%) y el Tipo II (0,4%). El foramen apical estaba situado en posición central en la mayoría de los dientes, 70,2% y 66,8% en los caninos maxilares y mandibulares, respectivamente. La ocurrencia de dos raíces en los caninos mandibulares es del 3,8% y la separación del conducto radicular se encontró en el tercio medio y cervical de la raíz en el 53,8% y el 46,2%, respectivamente. No se observó ninguna diferencia estadística significativa en el efecto del sexo y la edad sobre la incidencia de la morfología del conducto radicular y la posición del foramen apical. Debido a la diversa morfología y a la posible presencia de un segundo conducto en los dientes caninos entre la subpoblación turca, los odontólogos deberían realizar los tratamientos endodónticos con mayor cuidado...
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB